2001
DOI: 10.1007/s11745-001-0706-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cleavage products by autoxidation of lycopene

Abstract: The cleavage products formed by autoxidation of lycopene were evaluated in order to elucidate possible oxidation products of lycopene in biological tissues. Lycopene solubilized at 50 microM in toluene, aqueous Tween 40, or liposomal suspension was oxidized by incubating at 37 degrees C for 72 h. Among a number of oxidation products formed, eight products in the carbonyl compound fraction were identified as 3,7,11 -trimethyl-2,4,6,10-dodecatetraen-1-al, 6,10,14-trimethyl-3,5,7,9,13-pentadecapentaen-2-one, acyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 46 publications
3
45
1
1
Order By: Relevance
“…Bixin aldehyde (C 24 -dialdehyde), the intermediate in the biosynthesis of the plant pigment annatto, is formed by enzymatic cleavage of lycopene by a lycopene dioxygenase (2). Autooxidation of lycopene can also produce aldehyde products of different chain lengths by oxdative cleavage of lycopene (8). Here, we report the biosynthesis of carotenoid aldehydes by enzymatic oxidation of the linear end(s) of the carotenoid backbone.…”
Section: Discussionmentioning
confidence: 98%
“…Bixin aldehyde (C 24 -dialdehyde), the intermediate in the biosynthesis of the plant pigment annatto, is formed by enzymatic cleavage of lycopene by a lycopene dioxygenase (2). Autooxidation of lycopene can also produce aldehyde products of different chain lengths by oxdative cleavage of lycopene (8). Here, we report the biosynthesis of carotenoid aldehydes by enzymatic oxidation of the linear end(s) of the carotenoid backbone.…”
Section: Discussionmentioning
confidence: 98%
“…Utilizing various oxidizing systems and in vitro experiments, scientists have demonstrated lycopene’s susceptibility to cleavage, and identified unique oxidative products of lycopene. After incubating lycopene under atmospheric oxygen at 37 °C for 72 h, Kim et al identified eight oxidative products (3,7,11-trimethyl-2,4,6,10-dodecatetraen-1-al,6,10,14-trimethyl-3,5,7,9,13-pentadecapentaen-2-one, acyclo-retinal, apo-14â€Č-lycopenal, apo-12â€Č-lycopenal, apo-10â€Č-lycopenal, apo-8â€Č-lycopenal, and apo-6â€Č-lycopenal) [157]. Utilizing another oxidizing system, Caris-Veyrat et al identified eight apolycopenals and three apolycopenones generated from oxidation of lycopene [158].…”
Section: Effects Of Tomato and Lycopene Consumption Against Nash Amentioning
confidence: 99%
“…Nonetheless, the challenge is that numerous tomato carotenoids such as ÎČ-carotene and lycopene are particularly sensitive to degradation in cell culture systems [63-67]. Thus, it is a challenge to elucidate the roles of the carotenoids in vitro although the polyphenols are comparatively easy to examine in cell culture.…”
Section: Tomatoes and Prostate Cancermentioning
confidence: 99%